Identification of characteristic genes in cutaneous squamous cell carcinoma based on weighted gene co-expression network analysis - Xiao, Qipeng; Xu, Pengfei; Xu, Wenjun; Song, Qiuhe; Mao, Yousheng (Frontiers in Genetics, 2025)
ObjectiveThis study aims to identify characteristic genes associated with cutaneous squamous cell carcinoma (cSCC).MethodsDifferentially expressed genes (DEGs) and hub genes in key module were identified using the limma package and weighted gene co-expression network analysis (WGCNA) in R software, respectively. The intersection of these genes was then subjected to LASSO regression to pinpoint characteristic genes. The correlation between immune cell infiltration and these characteristic genes was further elucidated using single-sample Gene Set Enrichment Analysis and Spearman correlation analysis.ResultsA total of 113 DEGs were identified, along with their associated biological pathways. From this pool, five characteristic genes—ADH1B, CCL27, ID4, LRP4 and S100A9—were selected and validated. Immune infiltration analysis revealed significant correlations between these genes and various immune cell types, particularly with CCL27, ID4, LRP4 and S100A9.ConclusionThe identification of characteristic genes for cSCC provides valuable insights into its molecular mechanisms. The correlations between these genes and immune cell infiltration suggests their potential roles in tumor immunity.